“KITA KAN BEDA!”: PERSAMAAN REMAJA PEREMPUAN MUSLIM DAN KRISTEN DI LANGSA, ACEH - Muhammad Ansor (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2014)
This article explores the similarities and differences in the responses of Christian and Moslem teenage girls in Langsa to the discourse of clothing and the regulation of the body in Islamic law. Using Bourdieu’s concept of ‘habitus’ and Scott’s concept of ‘hidden transcripts’, this paper aims to explain why Muslim and Christian teenagers in Langsa have had a similar response to the discourse of clothing and the regulation of the body despite religious differences and how their resistance a is revealed in everyday behavior. This article argues that the similarities of their responses are a result of the shared socio-cultural spaces and political circumstances. Meanwhile, the differences expressed in their daily life are due to the religious values that they hold, especially the Christians as they are a minority amongst Aceh’s Muslim majority who have imposed a dress code that reflects the collective identity of Acehnese women.